Distributed RFID–GSM Warning Architecture for Railway Safety: Design and Evaluation in Resource-Constrained Environment - Billy Sam; Yaw Amankrah Sam-Okyere; Emmanuel Osei-Kwame; Wisdom Elikplim Korkortsi; Daniel Goddard Brookman; Ramatu Al-hasan (Applied Engineering, Innovation, and Technology, 2026)
Railway safety in resource-constrained environments, such as Ghana's degraded rail network, faces significant challenges due to obsolete infrastructure, single-track operations, and reliance on human vigilance, leading to high rates of collisions and level-crossing accidents. This study proposes a distributed RFID-GSM warning architecture as a low-cost, decentralized solution independent of legacy signaling systems. The system deploys stationary sensor nodes along rail approaches, utilizing RC522 RFID modules for precise train detection at 30 km, 20 km, and 10 km zones from critical junctions. An ATmega328P microcontroller processes detection triggers, activating hierarchical alerts: SMS notifications via SIM800L GSM for remote warnings at farther zones, and local actuators (buzzer and LED) for immediate intervention at 10 km. The design emphasizes affordability, simplicity, and robustness, leveraging existing cellular networks to mitigate human errors without requiring infrastructure upgrades. The architecture was modeled and simulated in Proteus Professional software, demonstrating accurate sequential detection, SMS transmission, and actuator activation. Reliability metrics, including detection probability (>90% within optimal range), SMS latency (3-8 seconds), and on-time delivery, confirm viability in low-speed, remote settings. Comparative analysis highlights advantages over GPS, LoRaWAN, or track circuits in cost and deployability. This approach provides a scalable digital safety layer, enhancing operational resilience and reducing accident risks in developing regions' marginalized rail networks.